Advanced treatment of secondary effluent from wastewater treatment plant by a newly isolated microalga Desmodesmus sp. SNN1 - Wang, Pengchong; Shao, Yahui; Geng, Yun; Mushtaq, Rubina; Yang, Wenlong; Li, Mei; Sun, Xiuqin; Wang, Hongbo; Chen, Gao (Frontiers in Microbiology, 2023)
Secondary effluents contain considerable amounts of nitrogen and phosphorous, which if dumped untreated can cause eutrophication of the receiving water bodies. Microalgae can remove these nutrients and other pollutants from the wastewater effluents and play an effective role in the secondary effluent treatment. In this study, six microalgae strains (SNN1, SNN2, SNN3, SNN4, SNS1 and SNS2) were isolated and screened from the water and mud of Yingxue Lake of Shandong Jianzhu University, and their efficiencies for the removal of COD, NH4+-N, TN and TP in the secondary effluent were assessed. By comparing the growth conditions of different algal strains in domestic sewage, we found that SNN1 (identified and named as Desmodesmus sp. SNN1) has the highest efficiency for biomass accumulation and sewage purification. Hence, the algal strain SNN1 was selected for further screening experiments. The strain showed higher biomass yield and better nutrient removal rate when the pH of secondary effluent was 9.0 and the initial inoculum concentration (optical density at 680 nm) of algal strain was 0.4. After 12 days of treatment, the concentrations of COD, NH4+-N, TN and TP in the secondary effluent were 31.79 mg/L, 0.008 mg/L, 8.631 mg/L and 0.069 mg/L, respectively. Therefore, SNN1 with the removal rates of 52.69% (COD), 99.99% (NH4+-N), 89.09% (TN) and 95.30% (TP) displayed its high potential in nutrient removal. In addition, it also yielded 6.65 mg/L of chlorophyll a and 168.33 mg/L of lipids. These results demonstrated that this strain exhibited an effective treatment capacity for secondary effluent and microalgal oil production. This study is helpful to provide a strategy for the resource utilization of secondary effluent and the conservation of freshwater resources required by microalgae culture.